High-performance MPPT control of DFIG with optimized flux reference in presence of nonlinear magnetic characteristic - Youssef Majdoub; Ahmed Abbou; Mohamed Akherraz (Institute of Advanced Engineering and Science, 2022)
In recent years, an expansive research exertion has been devoted to the control for aeorogenerators conforming of a Doubly Fed Induction Generator (DFIG) coupled to a wind turbine. Most preceding controllers based on standard models (whose magnetic induction characteristic is considered linear and iron losses have not been taken into account). Since such a magnetic characteristic is nonlinear in practice, this work develops a variable speed control strategy on the basis of a DFIG model in presence of nonlinear magnetic characteristic and iron losses. The main contribution of this paper is to present a high-performance maximum power point (MPPT) control of DFIG based on rotor flux optimization, designed to reach an optimal operational conditions. Of the foregoing, the control goal is twofold: i) minimization of the stator and rotor currents circulating by controlling the rotor flux for a maximum electromagnetic torque; ii) captured the maximum wind power to insure the attainment of MPPT. The performances of the proposed command has been studied theoretically and validated by simulation studies with Matlab/Simulink.